Hull form distortion method for planing craft - 406549 Hud Hj. Khalid (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering (Marine Technology)) - Universiti Teknologi Malaysia, 2003